2000
DOI: 10.1002/1099-0682(200012)2000:12<2597::aid-ejic2597>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Six-Coordinate Ruthenium(II) Complexes Containing Unsymmetrical 1,2-Bis(phosphanyl)ethanes and 1-Arsanyl-2-phosphanylethanes as Ligands

Abstract: The bis(η3‐2‐methallyl)ruthenium(II) complexes [Ru(η3‐2‐MeC3H4)2(κ2‐Ph2PCH2CH2PR2)] [R = iPr (2), Cy (3)] were prepared from the cycloocta‐1,5‐diene derivative [Ru(η3‐2‐MeC3H4)2(η4‐C8H12)] (1) and the unsymmetrical 1,2‐bis(phosphanyl)ethanes Ph2PCH2CH2PR2. The As,P analogue [Ru(η3‐2‐MeC3H4)2(κ2‐Ph2PCH2CH2AstBu2)] (4) was obtained by the same route. The reaction of 2 with hexafluoroacetylacetone afforded the chelate compound [Ru(κ2‐[F6]acac)2(κ2‐iPr2PCH2CH2PPh2)], whereas treatment of 2 and 3 with pentachloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Alternatively, breaking the Ru···Br interaction in trans - 5a by constraining the Ru−O−C−C Ar dihedral angle to 90°, and reminimizing, restores the chelated structure. Precedents for this coordination mode are found in other o -haloaryloxide complexes, including Ru(κ 2 - O,Br -2,4,6-OC 6 H 2 Br 3 )(PPh 3 ) 2 (Ru−Br = 2.63 Å), Ru 3 (CO) 8 (κ 2 - O,Cl -OC 6 H 4 Cl) 2 , CpRu(κ 2 - O,Cl -OC 6 Cl 5 ), Ru(κ 2 - O,Cl -OC 6 Cl 5 ) 2 (κ 2 - P,P -Ph 2 PCH 2 CH 2 P i Pr 2 ), and Ru(κ 2 - S,F -SC 6 F 5 )(SC 6 F 5 )(PMe 2 Ph) 2 …”
Section: Resultsmentioning
confidence: 82%
“…Alternatively, breaking the Ru···Br interaction in trans - 5a by constraining the Ru−O−C−C Ar dihedral angle to 90°, and reminimizing, restores the chelated structure. Precedents for this coordination mode are found in other o -haloaryloxide complexes, including Ru(κ 2 - O,Br -2,4,6-OC 6 H 2 Br 3 )(PPh 3 ) 2 (Ru−Br = 2.63 Å), Ru 3 (CO) 8 (κ 2 - O,Cl -OC 6 H 4 Cl) 2 , CpRu(κ 2 - O,Cl -OC 6 Cl 5 ), Ru(κ 2 - O,Cl -OC 6 Cl 5 ) 2 (κ 2 - P,P -Ph 2 PCH 2 CH 2 P i Pr 2 ), and Ru(κ 2 - S,F -SC 6 F 5 )(SC 6 F 5 )(PMe 2 Ph) 2 …”
Section: Resultsmentioning
confidence: 82%
“…4 After we prepared at the beginning of these studies a variety of rhodium(I) complexes with iPr 2 PCH 2 PR 2 (R = Ph, Cy) and iPr 2 PCH 2 AsR 2 (R = iPr, tBu) as ligands, 2,3 we later extended this work to corresponding ruthenium(II) compounds 5 and included, for comparison, also unsymmetrical 1,2-bis(phosphino)ethanes and 1-arsino-2-phosphinoethanes as coordinating units. 6,7 In the context of these studies we also observed that the stepwise reaction of [( 6 -p-cym)RuCl 2 ] 2 (cym = cymol) with Ph 2 PCH 2 CH 2 tPBu 2 and AgPF 6 leads to the formation of a hetero-tetranuclear Ru 2 Ag 2 compound in which the unsymmetrical bidentate ligand binds in a bridging mode. 6 Taking into consideration that rhodium complexes with optically active phosphine ligands are powerful tools not only in hydrogenation reactions but also in other parts of asymmetric organic synthesis, we decided to prepare a series of compounds [Rh( 4 -C 8 H 12 )(L-L)]PF 6 where L-L is an unsymmetrical and/or chiral bis(phosphino)methane, 1,2-bis(phosphino)ethane, 1-arsino-2-phosphinoethane or 1,3-bis(phosphino)propane.…”
mentioning
confidence: 77%
“…Results for the hydrogenation of -acetamidocinnamic acid methylester (ACM) at 1 bar pressure of H 2 in iPrOH (entry[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and in THF (entry[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] with complexes 12a-h as catalyst precursors a…”
mentioning
confidence: 99%